Analysis of Online Fraud Crimes in Buying and Selling Roblox Accounts on Social Media (Facebook) Based on the ITE Law - Safitri Handayani; Sri Pramudya Wardhani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of information technology and the increasing popularity of online games, particularly Roblox, have led to the emergence of the practice of buying and selling game accounts through social media such as Facebook. These transactions are generally conducted informally without adequate legal protection mechanisms, thus opening up opportunities for fraud. This study aims to analyze the types of fraud that occur in the buying and selling of Roblox accounts on Facebook and examine the criminal sanctions stipulated in